2017
DOI: 10.1038/s41598-017-06715-w
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Endogenous and Exogenous Spatial Attention on Decision Confidence

Abstract: Spatial attention allows us to make more accurate decisions about events in our environment. Decision confidence is thought to be intimately linked to the decision making process as confidence ratings are tightly coupled to decision accuracy. While both spatial attention and decision confidence have been subjected to extensive research, surprisingly little is known about the interaction between these two processes. Since attention increases performance it might be expected that confidence would also increase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…Two studies found that voluntary attention increased confidence 27,28 ; one found that voluntary but not involuntary attention increased confidence 30 ; and another found no effect of voluntary attention on confidence 29 . This last result has been attributed to response speed pressures 27,30 . Three other studies suggested an inverse relation between attention and confidence, though these used rather different attention manipulations and measures.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Two studies found that voluntary attention increased confidence 27,28 ; one found that voluntary but not involuntary attention increased confidence 30 ; and another found no effect of voluntary attention on confidence 29 . This last result has been attributed to response speed pressures 27,30 . Three other studies suggested an inverse relation between attention and confidence, though these used rather different attention manipulations and measures.…”
Section: Discussionmentioning
confidence: 89%
“…Perhaps, for example, performance of the Bayesian model was superior not because observers changed their categorization behavior, but because they rated their confidence based on the attention condition, which they knew explicitly. Given the mixed findings on the relation between attention and confidence [27][28][29][30] , and the proposal that perceptual decisions do not account for attention 13 , such a finding would not be trivial (see Discussion); but it would warrant a different interpretation than if category decision boundaries also depended on attention. We fit the four models to the category choice data only and again rejected the Fixed model (Figure S5a,b; Tables S3, S4).…”
Section: Resultsmentioning
confidence: 96%
“…Perhaps, for example, performance of the Bayesian model was superior not because observers changed their categorization behavior but because they rated their confidence based on the attention condition, which they knew explicitly. Given the mixed findings on the relation between attention and confidence (30)(31)(32)(33) and the proposal that perceptual decisions do not account for attention (13), such a finding would not be trivial (see Discussion), but it would warrant a different interpretation than if category decision boundaries also depended on attention. We fit the four models to the category choice data only and again rejected the Fixed model (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Despite attention's large influence on visual perception (8), only a handful of studies have examined its influence on visual confidence, with mixed results. Two studies found that voluntary attention increased confidence (30,31), one found that voluntary but not involuntary attention increased confidence (33), and another found no effect of voluntary attention on confidence (32). This last result has been attributed to response speed pressures (30,33).…”
Section: Discussionmentioning
confidence: 98%
“…Distinctive studies have also concluded that task priors are decisive in that respect [Buswell, 1935] [Navalpakkam and Itti, 2005] [Tatler et al, 2006] [Castelhano et al, 2009] [Greene et al, 2012] [Borji and Itti, 2014]. Goal-directed tasks proved to be able to condition eye movement behavior enhancing visual attention processing [Posner, 1980] [Jonides, 1981] [Huk and Heeger, 2000] [Kurtz et al, 2017]. That might suggest that visual search tasks could minimize such eye-movement patterns produced by endogenous top-down mechanisms [Horowitz and Wolfe, 1998] , by increasing induced attention towards salient targets (combining both saliency and relevance to influence eye guidance towards these regions).…”
Section: Task Relevancementioning
confidence: 99%